An Investigation of Predictors of Life Satisfaction among Overseas Iranian Undergraduate Students - Razieh Tadayon Nabavi; Mohammad Sadegh Bijandi (Educational Process: International Journal)
In recent years, many young people have gone overseas to study and live at least temporarily in new countries that maybe quite different to their homeland. The aim of this study was to determine the predictors of life satisfaction among Iranian undergraduate students studying at Malaysian private universities. A total of 361 undergraduate students were identified as respondents of this study by using Multi-Stage random sampling technique. The results of the study showed that the Iranian undergraduate students were moderately satisfied with their overseas student life. Findings also showed that the results of multiple regression analyses indicated social support emerged as the strongest unique predictor of life satisfaction, followed by academic achievement, and adjustment. Findings revealed that 44.8% of the variability in life satisfaction could be predicted by social support, academic achievement, and adjustment. The results also indicated that social support significantly mediated the effect of loneliness on life satisfaction.